2002
DOI: 10.1111/j.1651-2227.2002.tb00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental assessment of preterm and term children at 18 months: reproducibility and validity of a postal questionnaire to parents

Abstract: Aim: To examine the degree of agreement between the paediatrician's assessment and parental reporting of infants’development using a postal questionnaire. Methods: The developmental status of 241 infants in the charge of 9 community paediatricians or discharged from one Neonatal Intensive Care Unit (NICU) was assessed by their parents 18 mo after delivery, using a postal questionnaire regarding child's height, weight, respiratory, hearing and vision problems, and items taken mainly from the Griffiths’Developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 22 publications
2
20
0
2
Order By: Relevance
“…However, in the years after the attainment of motor milestones, parents are likely to remember the age of attainment with great precision . Furthermore, one study has shown that parental assessment of children's motor development is often consistent with that of professionals . The mean ages at attaining the two milestones were consistent with findings in other studies .…”
Section: Discussionsupporting
confidence: 66%
“…However, in the years after the attainment of motor milestones, parents are likely to remember the age of attainment with great precision . Furthermore, one study has shown that parental assessment of children's motor development is often consistent with that of professionals . The mean ages at attaining the two milestones were consistent with findings in other studies .…”
Section: Discussionsupporting
confidence: 66%
“…A variety of questionnaires and assessment tools have been used. Agreement between parents and professionals is better for severe than for moderate disability 11,27–32 . In our study, the relatively poor agreement between parents and professionals may have been influenced by several factors, including small numbers and different interpretation of speech abilities.…”
Section: Discussionmentioning
confidence: 56%
“…study, however, were obtained by applying the questionnaire criteria to previously obtained clinical and psychometric data, rather than comparing clinical data with concurrently obtained questionnaire data, as done in the current study. Parent reports of the developmental status of neonatal intensive care unit graduates at 18 months were compared with the results of clinical assessment by community paediatricians by Bortolus et al., 23 who found a mean agreement of 93% between the two measures. Agreement was strongest for vision, hearing, and motor function but weak for language and behaviour items.…”
Section: Discussionmentioning
confidence: 99%